High Crimes and Misdemeanors in Presidential Impeachment - Brown, H. author. aut Link
IX, 238 p.
Keywords: US Constitution states that the President is subject to removal from office upon impeachment and conviction of treason, bribery and 'other high Crimes and Misdemeanors.' In this book, Brown examines history behind this clause as well as the impeachments of Presidents Johnson, Nixon and Clinton.